Isolation and characterisation of carotenoid biosynthetic genes from Vitis vinifera - Taylor, Kerry Lyn (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Genetics. Plant Biotechnology))--University of Stellenbosch, 2007.